The Development of Artificial Intelligence and its Impact on the Financial Market - Tomaszek, Arkadiusz (Journal of Finance and Financial Law, 2022)
The purpose of this article. The aim of the article is to analyze selected issues related to artificial intelligence and its development, particularly its impact on the financial market, taking into account the opportunities and threats that artificial intelligence and its areas, such as machine learning or deep learning, pose to financial market participants. The research methods utilized in the study were used to evaluate the phenomenon on a macroeconomic scale. Methodology. The results of the research were based on the analysis of secondary data, such as source literature – both domestic and foreign, systems analysis of European Union legal acts, as well as the review of reports on the use of AI within the financial market. The paper is theoretical. The result of the research. The development of artificial intelligence in financial markets may provide an opportunity to gain competitive advantage, especially for financial market participants who aptly implement AI-based solutions in its initial phase. However, this entails both benefits and risks, the possible occurrence of which depends on many other factors.